ORIGIN OF LOW-CA PYROXENE IN AMOEBOID OLIVINE AGGREGATES: EVIDENCE FROM OXYGEN ISOTOPIC COMPOSITIONS - Krot A.N.; Fagan T.J.; Nagashima K.; Yurimoto H.; Petaev M.I. (My University, 2005)
Amoeboid olivine aggregates (AOAs) in primitive carbonaceous chondrites consist of forsterite (Fa<2), Fe,Ni-metal, spinel, Al-diopside, anorthite, and rare gehlenitic melilite (Åk<15). ~10% of AOAs contain low-Ca pyroxene (Fs1–3Wo1–5) that is in corrosion relationship with forsterite and is found in three major textural occurrences: (i) thin (<15 μm) discontinuous layers around forsterite grains or along forsterite grain boundaries in AOA peripheries; (ii) 5–10-μm-thick haloes and subhedral grains around Fe,Ni-metal nodules in AOA peripheries, and (iii) shells of variable thickness (up to 70 μm), commonly with abundant tiny (3–5 μm) inclusions of Fe,Ni-metal grains, around AOAs. AOAs with the low-Ca pyroxene shells are compact and contain euhedral grains of Al-diopside surrounded by anorthite, suggesting small (10%–20%) degree of melting. AOAs with other textural occurrences of low-Ca pyroxene are rather porous. Forsterite grains in AOAs with low-Ca pyroxene have generally ¹⁶O-rich isotopic compositions (Δ¹⁷O < −20‰). Low-Ca pyroxenes of the textural occurrences (i) and (ii) are ¹⁶O-enriched (Δ¹⁷O < −20‰), whereas those of (iii) are ¹⁶O-depleted (Δ¹⁷O = −6‰ to −4‰). One of the extensively melted (>50%) objects is texturally and mineralogically intermediate between AOAs and Al-rich chondrules. It consists of euhedral forsterite grains, pigeonite, augite, anorthitic mesostasis, abundant anhedral spinel grains, and minor Fe,Ni-metal; it is surrounded by a coarse-grained igneous rim largely composed of low-Ca pyroxene with abundant Fe,Ni-metal-sulfide nodules. The mineralogical observations suggest that only spinel grains in this igneous object were not melted. The spinel is ¹⁶O-rich (Δ¹⁷O ∼ −22‰), whereas the neighboring plagioclase mesostasis is ¹⁶O-depleted (Δ¹⁷O ∼ −11‰).
Keywords: Amoeboid olivine aggregates; chondrites; low-Ca pyroxene